Breast cancer mortality in Brazilian men: an age-period-cohort study - Casagrande Passoni Lopes, Lucas (Mastology, 2025)
Male breast cancer is a rare malignancy whose health impacts remain unknown, notably in countries like Brazil. The purpose of this article was to evaluate breast cancer mortality in Brazilian men by an age-period-cohort study. Methods: This ecological study evaluates the mortality of Brazilian men due to breast cancer using an age-period-cohort model. Data were sourced from the public, open-access Brazilian database DATASUS, available at https://datasus.saude.gov.br, covering the period from 1996 to 2021. Demographic data represent the total population of Brazilian males, while clinical data focus on patients whose cause of death was coded as 175 (ICD-9) or C50 (ICD-10). The age-period-cohort effects were analyzed following the classic model and its adaptations. The analysis was performed using R 4.4.0. Alpha® software. Results: It was noted an increasing mortality trend with aging, peaking in men over 80 years old. From 1996 to 2009, no statistically significant changes were observed in the hazard ratio (HR). However, from 2010 onward, a significant increase in HR was found, reaching a peak in 2020–2021 (HR 2.79634; 95%CI 2.37121–3.29770). A total of 34 birth cohorts (1919–2011) were analyzed. Cohorts from 1919–1964 and 1981–2011 did not show statistically significant results, while those from 1966–1979 exhibited a decreasing HR, with the lowest HR seen in the 1979 cohort (HR 0.91323; 95%CI 0.83545–0.99825). Conclusions: This study identifies a growing trend in male breast cancer mortality in Brazil, particularly after 2010, with variations across birth cohorts.